2007
DOI: 10.1111/j.1471-1842.2007.00688.x
|View full text |Cite
|
Sign up to set email alerts
|

Making a difference? Measuring the impact of an information literacy programme for pre‐registration nursing students in the UK

Abstract: Objectives : To investigate whether an information literacy programme for preregistration nursing students at a UK higher education institution is effective in developing their skills and confidence: examines students' skill levels, factors affecting their confidence, and relationships between skills, confidence and demographic characteristics. Methods : Quantitative and qualitative techniques were used: pre-and post-tests to measure changes in students' skills and self-assessed confidence levels after two key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 30 publications
0
22
1
Order By: Relevance
“…However, having in mind the whole picture of respondents' information literacy skills, the way they used information and evaluated it did not indicate a high level of skill. Therefore, the results of the present study are in conflict with many results reported in the relevant literature (Branch, 2003;Brunton, 2007;Craig & Corrall, 2007;Kai-Wah Chu & Law, 2008;Samson, 2010;Tramullas & Casabon, 2010;Urquhart & Rowley, 2007). In addition, more than half of the students claimed that they had not attended a library instruction program (62%) and also that they had never or very seldom consulted a librarian (63%).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…However, having in mind the whole picture of respondents' information literacy skills, the way they used information and evaluated it did not indicate a high level of skill. Therefore, the results of the present study are in conflict with many results reported in the relevant literature (Branch, 2003;Brunton, 2007;Craig & Corrall, 2007;Kai-Wah Chu & Law, 2008;Samson, 2010;Tramullas & Casabon, 2010;Urquhart & Rowley, 2007). In addition, more than half of the students claimed that they had not attended a library instruction program (62%) and also that they had never or very seldom consulted a librarian (63%).…”
Section: Discussioncontrasting
confidence: 56%
“…) in the information seeking process (Branch, 2003;Barrett, 2005;George et al, 2006;Griffiths & Brophy, 2005;Patitungkho & Deshpande, 2005;Vezzosi, 2009). In relation to the influential role of librarians, some studies have indicated the influence of library instruction or other information literacy programs on information seeking behavior (Branch, 2003;Brunton, 2007;Craig & Corrall, 2007;Kai-Wah Chu & Law, 2008;Samson, 2010;Tramullas & Casabon, 2010;Urquhart & Rowley, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“… Self‐confidence. Craig and Corrall note increased self‐confidence when studying information literacy skills of nurses in the UK 35 …”
Section: Resultsmentioning
confidence: 99%
“…These positive findings provided justification for scores of curriculumintegrated nursing IL programs and worked their way into many subsequent studies (Barnard, Nash, & O'Brien, 2005;Brettle, 2003;Brettle & Raynor, 2013;Carter-Templeton, 2011;Craig & Corrall, 2007;Eimas & Barton, 2001;Grant & Brettle, 2006;Jette, Tribble, Gagnon, & Mathieu, 2010;Meneses Placeres, 2008a, 2008bMorgan, Fogel, Hicks, Wright, & Tyler, 2007;Nodarse Rodríguez, 2005;Rush, 2008;Saranto & Hovenga, 2004;Shorten, Wallace & Crookes, 2001;Tronstad, Phillips, Garcia, & Harlow, 2009;Weinert & Palmer, 2007;Wright & McGurk, 2000). Authors occasionally described the work with words like "seminal" (Craig & Corrall, 2007).…”
Section: Positive Effect Of Il Instructionmentioning
confidence: 84%